PERANCANGAN BLADE AIRFOIL DENGAN BANTUAN PROGRAM TRANSFORMASI JOUKOWSKY - Rusianto, Toto; Setyaningsih, Emy (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2014)
Design cross section of wind turbine blades with airfoil cross-section can be made from a mathematical approach. The mathematical formula was discussed for airfoil shape from Joukowsky equation, that was developed by Nikolai Zhukovsky Egorovich. The problems would appear if used the Joukowsky equation settlement for design with manual, it could take a long time. The problem solving for the mathematical could use graphic user interfaces (GUI) program and the design for implementation could use computer aided design (CAD) program. The Joukowsky transformation was performed by conformal mapping through the transformation of a complex function from one coordinate system to another, which circle shape was transformed to airfoil shape. Ideal airfoil shape was obtained with observed of the transformation radius and center of the circle.